Strategi Komunikasi Dakwah Program Ngobrol Perkara Masjid Al-Hijrah Sukajaya Palembang - Saputra, Deni Hariyadi; Razzaq, Abdur; Hamandia, Muhammad Randicha (Pubmedia Social Sciences and Humanities, 2024)
This research seeks to reveal the Da'wah Communication Strategy of the Program for Chatting about Islam, Faith, Ihsan, Al-Hijrah Mosque Sukajaya Palembang. There are two problem formulations in this research. First, what are the activities besides chatting about Islamic matters at the Al-Hijrah Sukajaya Mosque, Palembang? Second, what is the communication strategy for the Da'wah program for the Chat about Islamic Affairs program at the Al-Hijrah Mosque in Sukajaya, Palembang? This type of research is field research with a qualitative approach and analyzed using qualitative descriptive. The data collection technique that the author used in this research was observation, interviews and documentation techniques. The results of the research are that the Islamic Case Chat program is a program from the Al-Hijrah Mosque with a da'wah communication strategy carried out by the Islamic Case Chat program, namely that this program focuses on mobilizing the inner feelings and aspects of the Da'wah Partner's heart. By starting the activity with the recitation of Shalawat Jibril, Surah Yasin and Dhikr Tadriibul Zakaatil Qolbi Bil Ashwaati, creating a relaxed environment, they create opportunities for deep reflection and spiritual growth. Second, sending messages of advice and religious knowledge via WhatsApp and groups is an effective method for communicating with da'wah partners. This allows the delivery of messages that are planned and full of gentleness, as well as motivating them to study and take part in mosque activities. Third, inviting speakers or speakers who are experienced and competent in religious issues is an important strategy. These speakers can provide quality and useful presentations that support the da'wah message.